ANALISIS YURIDIS TERHADAP PEMBERIAN KEWARGANEGARAAN KEPADA PEMAIN SEPAK BOLA MELALUI MEKANISME NATURALISASI - Bagas Saputra; Nayla Syamrotul Azra; Zelda Savitri (Journal Of Law And Social Society, 2026)
Citizenship is a fundamental legal institution that establishes a reciprocal relationship between individuals and the state, thereby giving rise to mutual rights and obligations within a legal and political framework. In recent years, the practice of granting citizenship to foreign athletes in order to strengthen national sports teams has generated various debates concerning legality, national identity, and state sovereignty. This research aims to analyze the legal framework governing the naturalization of foreign football players and to examine the balance between the interests of improving sports performance and the principles of citizenship and state sovereignty. This study employs a normative legal research method that focuses on examining legal norms contained in statutory regulations, legal doctrines, and scholarly works. It applies statutory, conceptual, and international law approaches to assess the compatibility between national citizenship policies and global sports governance standards. The findings indicate that the naturalization of athletes, although legally permissible as a mechanism for acquiring citizenship, still requires strict legal procedures and careful policy considerations in order to maintain legitimacy and safeguard broader citizenship values. The novelty of this research lies in the integration of citizenship law studies, principles of sports law, and perspectives from international regulatory frameworks to provide a comprehensive legal analysis of athlete naturalization within national sports policy. This study emphasizes the importance of maintaining a balance between strategic interests in the development of sports achievements and the preservation of citizenship values, thereby contributing to the formulation of more coherent policies with a strong legal foundation in sports governance. Keywords: citizenship law; legal analysis; nationality policy; sports naturalization; state sovereign.